For a Geopolitical Instead of Technocratic Approach to the EU Enlargement Process: Addressing the Aftermath of the Lifted Bulgarian Veto - Kolozova, Katerina (Identities: Journal for Politics, Gender and Culture, 2023)
The paper argues that the European Commission and the Union itself ought to adopt a more hands-on political rather than technocratic approach to the issue of EU enlargement. In a context when Europe redefines geopolitics, including technology, science, education as well as combating climate change and digitalisation in its geopolitical self-repositioning, the issue of enlargement should be treated as an internal geopolitical concern of the European Union itself and not just as the concern of the applicant countries. Author(s): Katerina Kolozova Title (English): SFor a Geopolitical Instead of Technocratic Approach to the EU Enlargement Process: Addressing the Aftermath of the Lifted Bulgarian Veto Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 20, No. 1-2 (2023). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 60-67 Page Count: 8 Citation (English): Katerina Kolozova, "For a Geopolitical Instead of Technocratic Approach to the EU Enlargement Process: Addressing the Aftermath of the Lifted Bulgarian Veto,” Identities: Journal for Politics, Gender and Culture, Vol. 20, No. 1-2 (2023): 60-67.